f''(x) = [(25-x)^2 * (25-4x)]'
f"(x) = 2(25-x)*(-1)*(25-4x)+(25-x)^2*(-4) <--- used product and "core rule" (don't know if that's correct in English). Kjerneregelen.
f"(x) = (25-x)(8x-50)-4(25-x)^2
f"(x) = (25-x)[(8x-50)-4(25-x)] <---- where did the ^2 go, and where did the [ ] come from??
f"(x) = (25-x)(8x-50-100+4x)
f"(x) = (25-x)(12x-150)
That's what I'm wondering about. The ^2 in line 3... is suddenly gone in line 4. Looks like they changed it with [ ]. Why/how.... what?
f"(x) = 2(25-x)*(-1)*(25-4x)+(25-x)^2*(-4) <--- used product and "core rule" (don't know if that's correct in English). Kjerneregelen.
f"(x) = (25-x)(8x-50)-4(25-x)^2
f"(x) = (25-x)[(8x-50)-4(25-x)] <---- where did the ^2 go, and where did the [ ] come from??
f"(x) = (25-x)(8x-50-100+4x)
f"(x) = (25-x)(12x-150)
That's what I'm wondering about. The ^2 in line 3... is suddenly gone in line 4. Looks like they changed it with [ ]. Why/how.... what?